The safety and efficacy of second-generation cryoballoon ablation plus catheter ablation for persistent atrial fibrillation: A systematic review and meta-analysis. - Mengjiao Shao; Luxiang Shang; Jia Shi; Yang Zhao; Wenhui Zhang; Ling Zhang; Yaodong Li; Baopeng Tang; Xianhui Zhou (PLoS ONE, 2018)
Background Growing evidence suggests that second-generation cryoballoon ablation (2G-CB) is effective in patients with persistent atrial fibrillation (PerAF). The cornerstone of atrial fibrillation (AF) ablation is pulmonary vein isolation (PVI). The purpose of this study was to summarize the available data on the safety and mid-term (≥ 12 months) effectiveness of a 'PVI-only' strategy vs. a 'PVI-plus' strategy using 2G-CB in patients with PerAF. Methods We searched the PubMed, EMBASE and Cochrane library databases for studies on 2G-CB for PerAF. Group analysis was based on the ablation approach: 'PVI-only' versus 'PVI-plus', the latter of which involved PVI plus other substrate modifications. Studies showing clinical success rates at a follow-up (FU) of ≥ 12 months were included. Complication rates were also assessed. Data were analyzed by applying a fixed effects model. Results A total of 879 patients from 5 studies were analyzed. After a mid-term FU of 27 months, the overall success rate of 2G-CB for PerAF was 66.1%. In the 'PVI-plus' group, the success rate was 73.8%. In the 'PVI-only' group, the success rate was 53.6%. No heterogeneity was noted among studies (I2 = 0.0%, P = 0.82). Complications occurred in 5.2% of patients (P = 0.93), and the rate of phrenic nerve (PN) injury was 2.8% (P = 0.14). Vascular assess complications were the most frequent at 1.6% (P = 0.33). No death or myocardial infarction was reported. Conclusion 'PVI-plus' involving 2G-CB seems to be safe and effective for treating PerAF.